Unraveling host genetics and microbiome genome crosstalk: a novel therapeutic approach - Zhang, Qian; Schwarz, Dennis; Cheng, Yumei; Sohrabi, Yahya (Trends in molecular medicine, 2024)
The ability of the gut microbiome to adapt to a new environment and utilize a new metabolite or dietary compound by inducing structural variations (SVs) in the genome has an important role in human health. Here, we discuss recent data on host genetic regulation of SV induction and its use as a new therapeutic approach.
Keywords: Animals; genetics; lidé; metabolite; structural variation; zvířata; interakce mikroorganismu a hostitele; gut microbiome; střevní mikroflóra; ABO; Host Microbial Interactions; Gastrointestinal Microbiome; Humans